CuBi2O4 nanocrystals integrated with polyaniline nanobelt arrays for weak light photomultiplication type photodetector. Issue 1 (29th November 2022) - Singh, Anshika; Chauhan, Pratima; Verma, Arpit; Chandra Yadav, Bal
Abstract : Novel CuBi2 O4 nanocrystals incorporated in the polyaniline matrix utilized for the fabrication of a flexible and bio-compatible device for the detection of low-intensity photons by using a photomultiplication type photodetector. Abstract : In this paper, a novel flexible photodetector based on emerging p-type CuBi2 O4 and p-type conducting polymer polyaniline is fabricated. The conducting polymer is directly coated on the surface of CuBi2 O4 via a facile and low-cost in situ polymerization approach. The morphological investigation of CuBi2 O4 -polyaniline nanohybrid material shows that nanobelts and the material interface are responsible for the high rate of charge carrier generation. X-ray diffraction analysis confirmed that the inorganic material CuBi2 O4 intercalated in the polyaniline matrix. The I – V measurement was carried out on the prepared device in the range of −50 V to +50 V and the photoresponse at an illumination intensity of 50 μW cm −2 . The flexible device shows high-performance photodetection with a high external quantum efficiency (EQE) of 1.824 × 10 3 %, a high photoresponsivity of 5.381 A W −1 and a detectivity of 6.02 × 10 11 Jones at only 1 V. Because of the straightforward device design and low-cost fabrication process, this study offers a feasible way for manufacturing organic–inorganic high-performance low-intensity photon detectors.